Neither angels nor demons: women, crime, and victimization - Ferraro, Kathleen J. (The Northeastern series on gender, crime and law, 2006)
Introduction -- Blurred boundaries and the complexities of experience -- Irreconcilable differences : women's encounters with the criminal processing system -- Negotiating surreality -- The social reproduction of women's pain -- Demonic angels? : violence against abusers -- Angelic demons? : crimes of complicity -- Epilogue